0076 The Role of Preoptic Area GABAergic Axonal Projections to Tuberomammillary Nucleus in Sleep Homeostasis. (27th May 2020) - Maurer, J; Covarrubias, I; Baik, J; Weber, F; Chung, S
Abstract: Introduction: Sleep deprivation has profound widespread physiological effects including cognitive impairment, compromised immune system function and increased risk of cardiovascular disease. The preoptic area (POA) of the hypothalamus contains sleep-active GABAergic neurons that respond to sleep homeostasis. We have shown that activation of POA GABAergic axons innervating the tuberomammillary nucleus (TMN, GABAergic POA ->TMN ) are critical for sleep regulation but it is unknown if these projections modulate sleep homeostasis. Methods: To monitor in vivo neural activity of GABAergic POA ->TMN projection neurons during sleep deprivation and rebound, fiber photometry was used. GAD2-Cre mice ( n=6 ) were injected with AAV-DIO-GCaMP6S into the POA and an optic fiber was implanted into the TMN. An electroencephalogram (EEG) and electromyography (EMG) implant was mounted upon the skull to identify brain states. Calcium activity was measured for six hours starting at ZT4. Each mouse was recorded for three days to establish baseline sleep calcium activity with at least two days between sessions. During sleep deprivation sessions, an experimenter sleep deprived each mouse starting at ZT0 for six hours by gently brushing the animal with a small paintbrush to maintain wakefulness and minimize the stress to the animal. Results: During baseline sleep recordings, GABAergic POA ->TMN projection neurons are most active during sleep (NREM and REM) which is maintained until wake onset. As sleep pressure increases, GABAergic POA ->TMN projection neurons display gradual increase in neural activity compared to time-matched points during baseline sleep recordings. Once mice were permitted to enter sleep rebound, GABAergic POA ->TMN projection neurons gradually displayed decreased activity as sleep pressure eased. Conclusion: GABAergic POA ->TMN projection neurons show a strong increase in activity to drive homeostatic sleep need during periods of increased sleep pressure but subside once this pressure is reduced. Support: This work is supported by NIH grant R01-NS-110865.